PENERAPAN METODE PEMBELAJARAN MIND MAPPING UNTUK MENINGKATKAN KETERAMPILAN BERBICARA PADA SISWA KELAS III SDN SIDOKLUMPUK SIDOARJO - Azizatul Imtihana; Eviyanti Asmaul Kusnah (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2022)
This research aims to improve students' speaking skills using the mind mapping method in compiling the main ideas of a concept into a mind map that is easily accessible by students. Lack of enthusiasm, confidence, and good intonation of pronunciation in students which causes less than optimal in speaking skills. The object of this research is the third grade students of SDN Sidoklumpuk Sidoarjo. This type of research is Classroom Action Research (CAR). The term in English is Classroom Action Research (CAR), which is a research activity carried out in the classroom using a research design according to Kemmis and Mc. Taggart. The data collection techniques used by the research are interviews, tests and observations. In the first cycle there were 5 students who finished with a score of 75 and 23 students who had not finished, the presentation of the success criteria for the first cycle was 17.8% and the results of observing student activities in the first cycle learning process were 56.25%. Furthermore, in the second cycle there were 25 students who achieved the success criteria, 3 students had not reached the success criteria, the student activity in the second cycle learning process was 93.75%. Thus, the implementation of learning using the mind mapping method can improve the speaking skills of third grade students at SDN Sidoklumpuk Sidoarjo